2005
DOI: 10.1097/01.mbc.0000188413.32859.b2
|View full text |Cite
|
Sign up to set email alerts
|

Cancer procoagulant in patients with adenocarcinomas

Abstract: Cancer procoagulant (CP) is a cysteine proteinase that may be produced by malignant and foetal tissue. The possible role of CP in the pathogenesis of cancer-related thrombosis has been suggested recently. The purpose of the study was to evaluate coagulation prothrombotic markers and their relation to CP concentration in the blood of patients with gastrointestinal adenocarcinomas (GIAC). The study group consisted of 45 patients with confirmed diagnosis of adenocarcinoma (stomach, 18 patients; colon, 27 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
1
16
0
2
Order By: Relevance
“…In the presence of factor V, cancer procoagulant may further enhance thrombin generation by up to 3-fold. Increased cancer procoagulant levels have been reported in patients with acute promyelocytic leukemia, malignant melanoma, and cancers of the colon, breast, lung, and kidney, and there is in vitro evidence that it may also be involved in metastatic potential [79–82]…”
Section: The Pathophysiology Of Thrombosismentioning
confidence: 99%
“…In the presence of factor V, cancer procoagulant may further enhance thrombin generation by up to 3-fold. Increased cancer procoagulant levels have been reported in patients with acute promyelocytic leukemia, malignant melanoma, and cancers of the colon, breast, lung, and kidney, and there is in vitro evidence that it may also be involved in metastatic potential [79–82]…”
Section: The Pathophysiology Of Thrombosismentioning
confidence: 99%
“…A recent clinical study evaluated prothrombotic markers and their relation to CP concentration in the blood of patients with gastrointestinal adenocarcinomas with or without metastatic disease. 40 The data suggested that CP is only a minor risk factor for deep venous thrombosis in such patients. However, more studies of this matter are needed.…”
Section: Tumor-associated Cysteine Proteinasementioning
confidence: 99%
“…Раковый прокоагулянт (РП), секретируемый опухолевыми клетками и отсутствующий в нормальных клетках, напрямую активирует Х-фактор. Повышенный уровень РП выявляется у больных с различными злокачественными опухолями [25,26]. Активация Х-фактора может происходить и неэнзиматическим путем под влиянием муцина, продуцируемого клетками аденокарциномы желудка и поджелудочной железы [27].…”
Section: механизмы паранеопластической тромбофилииunclassified